Tyrosol prevents glucocorticoid-induced skeletal muscle damage - Salucci, Sara; Burattini, Sabrina; Curzi, Davide; Burini, Debora; Zappia, Giovanni; Falcieri, Elisabetta (Italian Journal of Anatomy and Embryology, 2018)
Excessive oxidative stress is linked to the pathogenesis of a variety of skeletal muscle disor- ders [1]. Therefore, natural antioxidants could play a relevant role to counteract skeletal muscle damage. In particular, Tyrosol, a flavonoid present in virgin oil and known for its protective effect against oxidative injury in various cell models [2], could be active in skeletal muscle too, even if, until now, its effective antioxidant actvity, both in vitro and in vivo, has not been exten- sively studied in this tissue. Here, Tyrosol action has been investigated, through morpho-functional approaches, in C2C12 myotubes exposed to dexamethasone, a molecule usually used to mimic muscle wasting in vitro [3]. Dexamethasone-treated cells show a diffuse damage and, in particular, a reduced fiber size, if compared to control condition. In fact, if long and confluent myotubes progressively form- ing a larger fiber can be observed in control samples, those exposed to dexamethasone appear as immature, smaller syncytia. Moreover, differently from control cells, treated-myotubes show mitochondria alterations, characterized by disorganized cristae and loss of mitochondrial mem- brane potential and mass. Tyrosol administration before glucocorticoid treatment prevents mus- cle wasting and improves mitochondrial morphology and functions. Therefore, these preliminary data encourage the use of this natural antioxidant as “mito- chondrial nutrient”, able to delay mitochondrial dysfunctions and to prevent glucocorticoid- induced muscle atrophy. Further studies are in progress to highlight tyrosol molecular path- ways involved in muscle mass preservation. This work is supported by DiSB 2017 Enhancement Project, Urbino University.